ISLAMIC EDUCATION IN CIVILIZATION OF FASHION INDUSTRY: CLOTHES CONCEPT REFLECTION IN ISLAM - Ahmad Mustami (Ta'dib: Jurnal Pendidikan Islam, 2015)
This article discusses the concept Apparel in Islamic education. This was currently a lot of variety of fashion in dress. Although the general function of clothes was a human genitalia cover and protect the body from the heat of the sun. However hijab at this time not just cover the nakedness, but rather as a fashion style that became a common thing now was infecting the womenfolk including Muslim. Ranging from clothes, pants, until hijab began in innovation so as to attract the eye. Although it is not yet represent the shape and fashion model/standard clothes, but felt able to express Islamic education in the dressing (hijab) and a fashion model/Islamic clothing. Obviously keep on religious norms, ethical and moral teachings. Substance of clothing in Islam is polite in accordance with the values of Islamic Education.